The Real School Safety Problem : The Long-Term Consequences of Harsh School Punishment - Kupchik, Aaron (Book collections on Project MUSE., 2016)
Schools across the U.S. look very different today than they did a generation ago. Police officers, drug-sniffing dogs, surveillance cameras, and high suspension rates have become commonplace. The Real School Safety Problem uncovers the unintended but far-reaching effects of harsh school discipline climates. Evidence shows that current school security practices may do more harm than good by broadly affecting the entire family, encouraging less civic participation in adulthood, and garnering future financial costs in the form of high rates of arrests, incarceration, and unemployment. This text presents a blueprint for reform that emphasizes problem-solving and accountability while encouraging the need to implement smarter school policies.